2009
DOI: 10.7202/038318ar
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Anxiety in Taiwanese Student Interpreters

Abstract: Although anxiety has been found to be a key variable in both interpretation performance and second language (L2) acquisition, there has been virtually no dialogue between these two fields. In order to bridge this gap, this study investigated Taiwanese undergraduate student interpreters’ foreign language (FL) anxiety using Horwitz, Horwitz et al.’s (1986) Foreign Language Classroom Anxiety Scale. Results showed that (1) Taiwanese student interpreters did have FL anxiety despite the language facility expected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
3
21
0
5
Order By: Relevance
“…Using a situation-specific anxiety measure -the FLCAS -to examine student interpreters' anxiety, the present study found the students' FL anxiety was significantly and negatively related to their learning outcomes in interpretation courses, regardless of whether the influence of trait anxiety was statistically controlled or not. This finding is not only similar to the low but significant correlation between conference interpreters' psychological stress and performance quality found in the AIIC (2002) Workload Study, which, as noted before (Chiang 2009), has in effect taken a step in this direction by encompassing specific stressors of conference interpreting in the Evaluating stress section of its attitude questionnaire, although the term situation-specific was never used in the study, but also similar to the results regarding situation-specific L2 anxiety variables and L2 performance reported in the L2 anxiety literature (for a more comprehensive review, see Horwitz 2001). Given the fact that interpretation generally involves an L2, and the findings of the present study, it is only natural to suggest that L2 anxiety is inherent to the anxiety students experience in an interpretation classroom, and it is highly likely that interpretation learning anxiety shares some commonalities with L2 anxiety.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Using a situation-specific anxiety measure -the FLCAS -to examine student interpreters' anxiety, the present study found the students' FL anxiety was significantly and negatively related to their learning outcomes in interpretation courses, regardless of whether the influence of trait anxiety was statistically controlled or not. This finding is not only similar to the low but significant correlation between conference interpreters' psychological stress and performance quality found in the AIIC (2002) Workload Study, which, as noted before (Chiang 2009), has in effect taken a step in this direction by encompassing specific stressors of conference interpreting in the Evaluating stress section of its attitude questionnaire, although the term situation-specific was never used in the study, but also similar to the results regarding situation-specific L2 anxiety variables and L2 performance reported in the L2 anxiety literature (for a more comprehensive review, see Horwitz 2001). Given the fact that interpretation generally involves an L2, and the findings of the present study, it is only natural to suggest that L2 anxiety is inherent to the anxiety students experience in an interpretation classroom, and it is highly likely that interpretation learning anxiety shares some commonalities with L2 anxiety.…”
Section: Discussionsupporting
confidence: 74%
“…As already pointed out (Chiang 2009), although the definition of anxiety varies from study to study, most interpretation anxiety studies have treated the anxiety triggered by interpretation as a manifestation of other more general types of anxiety by utilizing trait anxiety scales, state anxiety, or a combination of both trait and state anxiety scales to measure it. However, these studies employing general anxiety measures have produced inconsistent findings regarding the relationship of anxiety to interpretation performance or achievement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the fact that interpreting generally involves one or even two L2s, research has not paid sufficient attention to the fact that future interpreters' anxiety might derive from the use of that L2 or from a combination of that use and the completion of the interpreting task (e.g. Chiang, 2009;Jiménez & Pinazo, 2001;Kurz, 1997). Although interpreting studies are to an extent interdisciplinary, "interpreter educators have often resisted contacts with the fields of foreign language teaching and Second Language Acquisition (SLA)" (Zannirato, 2008, p. 20).…”
Section: Introductionmentioning
confidence: 99%
“…The authors consider this option confusing and that it hampers the construction of the solid line of research on psychological factors that the field of interpreting requires. Thus, and following Chiang (2009), from here on, interpretation anxiety is used unless a distinction is intended.…”
Section: Introductionmentioning
confidence: 99%